DNA barcoding of commercially relevant marine fish species in Tunisian waters. (28th June 2022) - Francisco, Sara M.; Lima, Cristina S.; Moreira, Inês; Shahin, Adel A. Basyouny; Ben Faleh, Abderraouf
Abstract: DNA barcoding based on the cytochrome c oxidase subunit I ( COI ) gene in mitochondrial DNA has been adopted as a global biological identification system for animals due to its accuracy compared with other classical taxonomic methods. The objective of this study was to establish a reference library with generated barcodes. A total of 84 fish specimens belonging to 37 commercially important marine fish species, representing five orders, 14 families and 30 genera, were sampled along the Tunisian coast and barcoded for the first time, obtaining 637 bp sequences. The average Kimura 2-parameter (K2P) distances within species, genera and families were 0.52, 6.86 and 14.60%, respectively. The Maximum likelihood (ML) tree revealed distinct clusters in concurrence with the taxonomic status of the species. Our results confirmed the authentication of the barcode approach for the identification of the species examined and provide valuable information that would help ichthyologists to achieve better monitoring, conservation and management of fisheries in Tunisia.